PENGARUH RASIO LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2016-2020 - Ikfan Rahmananda; Rahmi Widyanti; Basuki Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the financial performance of telecommunicationscompanies listed on the Indonesia Stock Exchange. In this study, to analyze data for theperiod 2016 to 2020 in the form of financial statements consisting of a balance sheet, whichdescribes the company's financial condition, an income statement that describes thecompany's performance over a certain period of time, and a cash flow report that presentsinformation on cash inflows or outflows at the end of the year. a period. Ratio analysis isone of the techniques used in financial statements. This analysis is prepared by combiningthe figures in the income statement and balance sheet. The results of these ratios can be asource of information for interested parties such as managers and suppliers of capital aboutthe value of the company.The results of the financial ratio analysis during periods 2016-2020, the resultsobtained for the best liquidity ratio and solvency ratio values are owned by PT. TowerBersama Infrastructure, Tbk., PT. Trikomsel Oke, Tbk., and PT. Smartfren Telecom, Tbk.(2016-2018) and PT. Sarana Menara Nusantara, Tbk. (2019-2020). The results of theregression analysis simultaneously that the liquidity ratio, activity ratio, solvency ratio, andprofitability ratio have a positive and significant impact on the financial performance oftelecommunications companies and partially obtained liquidity ratios, solvency ratios andratios activity has a positive and significant effect, while the profitability ratio has anegative and insignificant effect on the financial performance of telecommunicationscompanies.